Potential outdoor recreation activities at Hutan Simpan Rotan Tunggal, Raub Pahang - Zulkarnain, Mohamad Ikhwan Afifi (2016)
Recreation opportunities are favorable environment and social circumstances that can satisfy the various recreation preferences of recreationist. Recreation opportunity can exist without demand. This study was conducted at Hutan Simpan Rotan Tunggal, Raub Pahang to identify the various recreation opportunities that is suitable to plan and manage this forest reserve as an ecotourism destination. Hutan Simpan Rotan Tunggal was chosen as the study site because of its unique features and forest characteristics. The study was conducted by performing a reconnaissance survey through on – site inventory survey and interviewed the ranger and officer at District Forestry Department. The main activity that already exists in this forest is hiking to the top of the forest reserve. Therefore, this study aimed to identify the other recreational recourses that can be suggested as recreation activities. Six planning zones were identified, and Outdoor Recreation Resources Inventory was carried out for each planning zone. The Outdoor Recreation Resources Inventory consists of five elements, namely the topography and physical characteristic, flora and vegetation, fauna and the local climate condition of the area. The Outdoor Recreation Resources Inventory data was summarized and presented into maps to highlight the potential recreation resources in Hutan Simpan Rotan Tunggal. Four recreation activities were proposed, according to the resources identified namely camping, nature walk, education on forest ecology and bird watching. The information gathered in this study can be used as a guide for the Forestry Department in developing Hutan Simpan Rotan Tunggal as an ecotourism destination.